Brites, Joana; Correia, Luís Miguel, coord. (2020). Obras públicas no Estado Novo. Coimbra: Imprensa da Universidade de Coimbra. 426 p., Il. ISBN digital 978-989-26-1894-4 - Almeida, Paulo (CEM – Cultura, Espaço & Memória, 2022)
.